2000
DOI: 10.1007/s005209900120
|View full text |Cite
|
Sign up to set email alerts
|

Randomised double blind crossover study comparing ondansetron, granisetron and tropisetron. A cost-benefit analysis

Abstract: The goals of this work were to compare the relative efficacy of ondansetron, granisetron and tropisetron in a randomised double blind crossover trial, evaluating objective, subjective and pharmacoeconomic parameters. To this end, 136 patients were enrolled, 120 of whom were eligible and evaluable. Each patient received three identical chemotherapy cycles with an antiemetic protocol which consisted in dexamethasone 20 mg i.v. and a tapering dose schedule for 4 days, and a single i.v. dose of an antiserotoninerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 78 publications
0
5
0
5
Order By: Relevance
“…Most of the local general hospitals have been making granisetron the standard pre-medication for chemotherapy for it is considered as the "latest" 5HT-3 antagonist. In fact, most of the previous studies comparing granisetron and ondansetron did not clearly demonstrate superiority of one agent over another (Barrajon, 2000;del Giglio et al, 2000;Jordan et al, 2007). From our observation, granisetron injection appears to be overprescribed for the low emetogenic chemotherapy (LEC) in these settings at the maximum dosage of 3mg (0.04mg/kg).…”
Section: Introductionmentioning
confidence: 60%
“…Most of the local general hospitals have been making granisetron the standard pre-medication for chemotherapy for it is considered as the "latest" 5HT-3 antagonist. In fact, most of the previous studies comparing granisetron and ondansetron did not clearly demonstrate superiority of one agent over another (Barrajon, 2000;del Giglio et al, 2000;Jordan et al, 2007). From our observation, granisetron injection appears to be overprescribed for the low emetogenic chemotherapy (LEC) in these settings at the maximum dosage of 3mg (0.04mg/kg).…”
Section: Introductionmentioning
confidence: 60%
“…None of the systematic reviews done so far (no inclusion of palonosetron) have clearly demonstrated superiority of one agent over another. These studies included a comparison of granisetron, ondansetron, tropisetron and dolasetron, using all studies as references rather than head-to-head trials [31], and meta-analyses of randomised trials comparing granisetron with ondansetron [32], granisetron or tropisetron with ondansetron [33]. A recently performed meta-analysis of more than 40 cisplatin and non-cisplatin based studies showed an equivalence of ondansetron and granisetron, a significant advantage for granisetron over tropisetron, and no clear advantage of ondansetron over tropisetron [34,35].…”
Section: Comparative Efficacy Of the Available 5-ht 3 -Receptor-antagmentioning
confidence: 99%
“…In addition to aprepitant and fosaprepitant meglumine, the subjects in this study received another anti-emetic selected from granisetron, azasetron and palonosetron. While granisetron and azasetron reportedly are as potent as ondansetron in terms of the anti-emetic effect [ 29 – 31 ], Hashimoto et al [ 32 ] reported that the CR rate in patients treated with a highly emetic regimen comprising CDDP at a dose of 50 mg/m 2 or higher tended to be lower in the granisetron group than in the palonosetron group (59.1 versus 65.7 %; P = 0.0539). Based on this result, palonosetron administration was included as a variable in our risk factor analysis but was found uninfluential.…”
Section: Discussionmentioning
confidence: 99%